Potential of Endophytic Bacteria in Controlling The Red Jabon Leaf Spot Pathogens In Vitro - Elis Nina Herliyana; Asmoro, Prayogo Probo; Abdul Munif (CELEBES Agricultural, 2023)
Plant pathogens pose a significant challenge to the cultivation of red Jabon (Anthocephalus macrophyllus) seedlings. Notably, the fungi Rhizoctonia sp. and Pestalotia sp. are responsible for the destructive red leaf spot disease on Jabon leaves. To combat these fungal pathogens, the use of endophytic bacteria has emerged as a potential alternative. Endophytic bacteria can be isolated from various plant sources, although their effectiveness in controlling forest plant pathogens like Jabon has not been thoroughly explored. This study aimed to assess the potential of endophytic bacterial isolates obtained from Pteris ensiformis (Isolates APE15, APE22, APE33, and APE35) in controlling the growth of Rhizoctonia sp. and Pestalotia sp. through in vitro experiments. The antibiosis activity of the endophytic bacteria against the pathogenic fungi was evaluated using the dual culture method on PDA media. The results revealed that among the four endophytic bacterial isolates, APE35 exhibited the highest inhibitory effect on Rhizoctonia sp. (86.79%) and Pestalotia sp. (67.5%), while isolate APE22 only inhibited the growth of Pestalotia sp. (55%). In contrast, isolates APE15 and APE33 were unable to suppress either fungus. The antibiosis activity of APE35 and APE22 resulted in abnormal hyphal growth of the pathogenic fungi, characterized by shriveled, bent, dark-colored, and coiled hyphae. Physiological characterization of the endophytic bacteria revealed their ability to produce protease, cellulase, catalase, and phosphate-dissolving enzymes. Additionally, these bacteria exhibited a Gram-positive nature. This study provides valuable insights into the potential of endophytic bacterial isolates from P. ensiformis (APE35 and APE22) as biological control agents for Rhizoctonia sp. and Pestalotia sp., the causative agents of red Jabon leaf spot disease.